2024
DOI: 10.3390/jcm13030646
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Maximum Monosyllabic Word Recognition as a Predictor of Speech Understanding with Cochlear Implant

Ronja Czurda,
Thomas Wesarg,
Antje Aschendorff
et al.

Abstract: Background: The cochlear implant (CI) is an established treatment option for patients with inadequate speech understanding and insufficient aided scores. Nevertheless, reliable predictive models and specific therapy goals regarding achievable speech understanding are still lacking. Method: In this retrospective study, 601 cases of CI fittings between 2005 and 2021 at the University Medical Center Freiburg were analyzed. We investigated the preoperative unaided maximum word recognition score (mWRS) as a minimum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…However, etiology is oftentimes unknown, and, therefore, only a subpopulation could potentially benefit from etiology as a predictive factor. Czurda and coworkers investigated the impact of the etiology and duration of hearing loss on WRS 65 (CI) [39]. In 60% of the 601 analyzed ears, they reported that the etiology was unknown.…”
Section: Limitations Of This Studymentioning
confidence: 99%
“…However, etiology is oftentimes unknown, and, therefore, only a subpopulation could potentially benefit from etiology as a predictive factor. Czurda and coworkers investigated the impact of the etiology and duration of hearing loss on WRS 65 (CI) [39]. In 60% of the 601 analyzed ears, they reported that the etiology was unknown.…”
Section: Limitations Of This Studymentioning
confidence: 99%